An algorithm for assessing the vitality of plant individuals and the vitality structure of phytopopulations (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Vitality analysis is often used as a tool for assessing the vitality state of individuals and plant populations. Using the example of the Allіaria petiolata populations and a typical model example, three stages of the vitality analysis are described in detail. At the first stage, a group of attribute characterizing the vital state of the individuals of the plant species under study is established. To assess the vitality of individuals, and then the populations as a whole, three (the standard procedure for vitality analysis) or more attribute are used. At the second stage, the vitality of each of the individuals included in the sample of the required volume is estimated, in accordance with strict mathematical algorithms - the values of the signs that are initially expressed in absolute values are transferred into units of one, the vitality of the individuals is determined. The viability of each individuals lies in the amplitude from 0 to 1,0 and the higher it is, the higher the vital state of this individual. In the basic algorithm of vitality analysis, the individuals in the population are divided into three classes by its vitality "a", "b" and "c". For this purpose, the range of values of the vitality of individuals that lie in the amplitude from 0 to 1 is divided into three equal zones: more than 0,66 - the highest class of vitality – class "a", the vitality of the individual from 0,33 to 0,66 – class "b " - intermediate and individuals whose vitality is less than 0,33, class "c" – individuals of the lower class of vitality. In accordance with the values of the vitality of individuals (Qindividual), they are assigned one or another class of vitality. At the third stage, an integral assessment of the vitality of populations is given. Depending on the ratio in the population of individuals of classes “a” and “b”, the population refers to one of three vitality types: prosperous, equilibrium or depressive. Unlike the vitality of individuals, the population's vitality lies in the amplitude of Q values from 0 to 0,5. This interval is divided into three equal parts: from 0 to 0,167, from 0,167 to 0,333 and from 0,333 to 0,500. The first of these intervals (Q is less than 0,167) corresponds to depressive populations, the second from 0,167 to 0,333 is the equilibrium one and the third (Q is greater than 0.333) is prosperous. Separate consideration is given to the possibility of modifying a typical algorithm for assessing the vitality of individuals and populations for plants of various life strategies, which indicates the flexibility of the methodology for assessing the vitality of individuals and populations.
Keywords: vitality, multidimensional evaluation, key features, Allіaria petiolata.